Photocatalytic performance of black titanium dioxide for phenolic compounds removal from oil refinery wastewater: nanoparticles vs nanowires - Nawaz, R. (Springer Science and Business Media Deutschland GmbH, 2022)
In this study, TiO2 nanoparticles (NPs) and TiO2 nanowires (NWs) were synthesized via modified solâgel and hydrothermal methods, respectively. The TiO2 NPs and TiO2 NWs were characterized employing various analytical techniques. The performance of TiO2 NPs and TiO2 NWs was evaluated and compared for phenolsâ removal from model oil refinery wastewater under visible light irradiation. The TiO2 NPs and TiO2 NWs were pure anatase crystalline phases with average particle size of 10.17Â nm and 6.82Â nm and a narrow bandgap of 2.41 and 2.66Â eV, respectively. 3D view surface plots confirm that the long-range atomic arrangement of the atom was intact, indicated by atomically flat surfaces. The recombination rate of electrons and holes was significantly lower in TiO2 NWs compared to TiO2 NPs. Both the samples were able to remove more than 90 of phenols from model oil refinery wastewater. Phenol removal from neutralized spent caustic took a longer time (300 min) compared to desalter effluent and tank water drain (<180 min). Phenol removal efficiency increased when TiO2 NPs and TiO2 NWs were employed combinedly. TiO2 NWs were highly stable, as suggested by their performance for photocatalytic removal of phenols after five consecutive cycles. Â© 2021, King Abdulaziz City for Science and Technology.